A Review of Newer Biologically Potent Pyridine Analogues - Mulla, Mohammed Zuber D.; Siddiqui, Nilofarnaznin M.; Patel, Navin B.; Patel, Vatsal M.; Shaikh, Faiyazalm M. (Current Bioactive Compounds, 2025)
Pyridine is a nitrogen-containing six-membered heterocycle that is used both independently and fused with other heterocyclic rings such as thiazole, thiophene, and most likely with imidazole having a wide range of biological applications. In this review, we report all possible applications of pyridine analogs for all possible diseases. Due to various medicinal applications, the pyridine scaffold has become a fascinating target for medicinal chemistry researchers globally. These particular properties like basicity, water solubility, hydrogen bond forming ability, stability, and small molecular size led researchers to pay more attention to the pyridine molecule with different geometries such as anticancer, antitubercular, anticonvulsant, fungal, bacterial, anti-inflammatory, antidepressant, antioxidant, anti-HIV, antidiabetic and against the COVID-19. This review encompasses all possible applications of pyridine analogs for various diseases.
Keywords: anticancer